Robotic-assisted gastrointestinal stromal tumor (GIST) resection with endoscopic transoral specimen retrieval (Gastrointestinal Cancer-NOSES Type IX): a case report and literature review - Wang, Lang; Zhang, Jing; Wang, Dehai; Zang, Yifeng; Zhu, Xianglin; Zhao, Shijun; Zhao, Cheng; Liang, Hao; Zhang, Jie; Ding, Yinlu (Frontiers in Oncology, 2025)
ObjectiveTo investigate the methodology and outcomes of Da Vinci robotic-assisted resection of gastrointestinal stromal tumors (GISTs) combined with endoscopic transoral specimen retrieval (GC-NOSES type IX), establishing a benchmark for minimally invasive treatment of GISTs.MethodsThis manuscript details a case involving a GIST situated on the posterior wall of the distal gastric body, adjacent to the lesser curvature, with a size of approximately 2.7 cm and exhibiting an intraluminal growth pattern. The tumor was effectively excised through robot-assisted GIST resection, complemented by endoscopic transoral specimen extraction (GC-NOSES type IX). The case is analyzed alongside pertinent literature and surgical perspectives.ResultsThe patient was admitted with “persistent abdominal discomfort persisting for over two months.” Preoperative enhanced abdominal CT reveals a gastric body lesion measuring approximately 2.7 centimeters, suggestive of a GIST. The patient underwent a successful robot-assisted resection of the GIST, with endoscopic transoral specimen extraction (GC-NOSES type IX). Postoperative histopathological analysis confirmed a GIST measuring 4.0 cm × 3.0 cm × 3.0 cm, classified as low-risk, with clear resection margins. Immunohistochemical profiling showed CD117 (+), CD34 (+), Desmin (-), DOG-1 (+), Ki67 (approximately 5% positive tumor cells), S-100 (-), SDHB (+), SMA (a few cells +), and SOX-10 (-).ConclusionGISTs are the most common mesenchymal tumors found in the gastrointestinal tract, with a predominant occurrence in the stomach. The primary treatment approach is R0 resection. There is a clear trend towards minimally invasive techniques. Robotic-assisted gastric GIST resection with endoscopic transoral specimen extraction (GC-NOSES type IX) has shown significant advantages in minimally invasive surgery. However, the esophagus’s unique anatomical structure necessitates careful selection of surgical indications, mastery of operative techniques, and excellent team coordination. Ensuring surgical safety is crucial to fully harness the minimally invasive benefits of this technique, thereby optimizing patient outcomes.